Trends and variability of polar mesopause region temperatures attributed to atmospheric dynamics and solar activity - Holmen, Silje Eriksen (UiT Norges arktiske universitet, 2016)
The mesopause region can be considered a "boundary region" between the neutral atmosphere, where atmospheric constituents and momentum are transported mainly by winds and turbulent eddies, and the ionosphere, where the main transport mechanism is molecular diffusion. In the mesopause, complex interactions between dynamics and photochemistry occur, and we are far from a complete understanding of these interactions. This thesis aims to better understand the processes responsible for the large temperature fluctuations we observe in the polar mesopause region, especially the effects of atmospheric circulation and wave activity from lower atmospheric layers. Investigations of trends have also been conducted. To carry out these investigations, we have derived and examined mesopause temperatures from two high-latitude locations: Tromsø (70°N, 19°E) and Longyearbyen (78°N, 16°E), and turbopause height only from Tromsø. A long-term change in turbopause height may be important for understanding processes that are responsible for redistribution of atmospheric constituents. We examined winter season variations in the hydroxyl (OH*) airglow temperature record from Longyearbyen and identified local temperature maxima in mid-January and mid-February, as well as a minimum in the transition between December and January. We also identified a number of statistically significant periodic oscillations in temperatures derived from the Nippon/Norway Tromsø Meteor Radar, with periods ranging from 9 days to a year. The seasonal variation showed higher temperatures and variability during winter compared to summer. We also found local temperature enhancements just after spring equinox and summer solstice. Temperature variability and seasonal variation may, to a large extent, be explained by the large-scale circulation in the middle atmosphere and corresponding wave activity. The trends for the Longyearbyen OH* airglow winter temperature series and meteor radar derived temperatures from Tromsø, both annual and summer trends, were estimated ...